ROHIS’ DA’WAH STRATEGY IN SHAPING STUDENTS’ ISLAMIC CHARACTER AT SMAN 1 SUNGGAL SENIOR HIGH SCHOOL - Aksha Maulana; Soiman Soiman (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2026)
This study aims to determine the strategies used by the Islamic Spirituality Club (Rohis) in shaping the Islamic character of students at Sunggal 1 Public High School. This study uses descriptive qualitative research. Data collection techniques were carried out through observation, interviews, and documentation, with the main informants being the head of Rohis and two active administrators. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Rohis da'wah strategy in shaping the Islamic character of students is planned and systematic through two forms of planning, namely short-term and long-term strategies. The short-term strategy began with an introduction to the organization through Ta'aruf Rohis activities as an effort to realize the characteristics of students as the target of da'wah. Furthermore, this strategy was realized through various religious and social activities, such as recitation (taklim), a program for students skilled in da'wah through kultum activities, and activities for students who care for the poor, which aimed to instill values of social care and empathy among students. Meanwhile, the long-term strategy is implemented through annual activities such as Islamic Holidays (PHBI), Hijab Day, and short Islamic boarding school programs, which serve as a means of strengthening Islamic values in the school environment. The strategies are supported by the role of supervisors, school policies, and adequate facilities; however, they are constrained by limited time, differences in students’ religious understanding, and the low interest of some students. This study concludes that the Rohis da’wah strategies at SMA Negeri 1 Sunggal are not merely oriented toward the implementation of religious activities but represent an integrated and contextual da’wah planning process aimed at sustainably developing students’ Islamic character.